Pengaruh Organizational Citizenship Behavior, Kepuasan Kerja Dan Komitmen Organisasi Terhadap Kinerja Karyawan (Studi Pada PT. Telkom Kepanjen) - Bella Saputri; Nur Hidayati; Restu Millaningtyas (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
Abstract This study aims to determine how the influence of Organizational citizenship behavior, job satisfaction and organizational commitment on employee performance at PT. Telkom Kepanjen 2021. In this study there are 3 (three) independent variables, namely organizational citizenship behavior, job satisfaction and organizational commitment. The dependent variable in this study is employee performance. The population in this study were all active employees of PT. Telkom Kepanjen in 2021 with a total of 36 employees. The sampling technique used was a saturated sample. The method of data collection in this study used the method of distributing questionnaires. The data analysis technique in this study used multiple linear regression with SPSS ver 18. The results showed that had a significant simultaneously organizational citizenship behavior, job satisfaction and organizational commitment effect on employee performance. Partially, organizational citizenship behavior has a significant effect on employee performance. Job satisfaction has a significant effect on employee performance. Organizational commitment has a significant effect on employee performance. Keywords: organizational citizenship behavior, job satisfaction, organizational commitment, employee performance